Inoculation with Bacillus megaterium CNPMS B119 and Bacillus subtilis CNPMS B2084 improve P-acquisition and maize yield in Brazil - de Oliveira-Paiva, Christiane Abreu; Bini, Daniel; de Sousa, Sylvia Morais; Ribeiro, Vitória Palhares; dos Santos, Flávia Cristina; de Paula Lana, Ubiraci Gomes; de Souza, Fabiane Ferreira; Gomes, Eliane Aparecida; Marriel, Ivanildo Evódio (Frontiers in Microbiology, 2024)
Phosphorus (P) is a critical nutrient for plant growth, yet its uptake is often hindered by soil factors like clay minerals and metal oxides such as aluminum (Al), iron (Fe), and calcium (Ca), which bind P and limit its availability. Phosphate-solubilizing bacteria (PSB) have the unique ability to convert insoluble P into a soluble form, thereby fostering plant growth. This study aimed to assess the efficacy of inoculation of Bacillus megaterium B119 (rhizospheric) and B. subtilis B2084 (endophytic) via seed treatment in enhancing maize yield, grain P content, and enzyme activities across two distinct soil types in field conditions. Additionally, we investigated various mechanisms contributing to plant growth promotion, compatibility with commercial inoculants, and the maize root adhesion profile of these strains. During five crop seasons in two experimental areas in Brazil, Sete Lagoas-MG and Santo Antônio de Goiás-GO, single inoculations with either B119 or B2084 were implemented in three seasons, while a co-inoculation with both strains was applied in two seasons. All treatments received P fertilizer according to plot recommendations, except for control. Both the Bacillus strains exhibited plant growth-promoting properties relevant to P dynamics, including phosphate solubilization and mineralization, production of indole-3-acetic acid (IAA)-like molecules, siderophores, exopolysaccharides (EPS), biofilms, and phosphatases, with no antagonism observed with Azospirillum and Bradyrizhobium. Strain B2084 displayed superior maize root adhesion compared to B119. In field trials, single inoculations with either B119 or B2084 resulted in increased maize grain yield, with relative average productivities of 22% and 16% in Sete Lagoas and 6% and 3% in Santo Antônio de Goiás, respectively. Co-inoculation proved more effective, with an average yield increase of 24% in Sete Lagoas and 11% in Santo Antônio de Goiás compared to the non-inoculated control. Across all seasons, accumulated grain P content correlated with yield, and soil P availability in the rhizosphere increased after coinoculation in Santo Antônio de Goiás. These findings complement previous research efforts and have led to the validation and registration of the first Brazilian inoculant formulated with Bacillus strains for maize, effectively enhancing and P grain content.